The Survival Rate Among Unvaccinated, First Dose, and Second Dose Brazilian Hospitalized and ICU COVID Patients by Age Group - Ramos, Rodrigo Henrique; Ferreira, Cynthia de Oliveira Lage; Simão, Adenilso (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2022: Anais do XXII Simpósio Brasileiro de Computação Aplicada à Saúde, 2022)
Brazil has a nationwide surveillance repository of severe acute respiratory disease for hospitalized patients. This repository has stored data for 1,177,151 hospitalized and ICU COVID-19 patients in 2021. In order to statistically validate the difference in the survival rate among unvaccinated, one dose, and two doses, we preprocess the data, divide it into age groups and between hospitalized and ICU patients. This work presents statistical evidence for hospitalized patients that lethality increase with age and decreases with vaccines, especially with the second dose. We found a significant difference among age groups and between hospitalized and ICU, indicating the need to separate these groups when analyzing lethality and comorbidities.